Effectiveness of Local Indigenous Rhizobacterial Isolates in Enhancing Resistance of Shallot (Allium cepa L.) to Fusarium oxysporum - Afa, Musadia; Mpia, La (Agro Bali : Agricultural Journal, 2025)
Fusarium wilt caused by Fusarium oxysporum remains a major limitation in shallot (Allium cepa L.) cultivation, severely reducing yield and crop quality. This study aimed to evaluate the effectiveness of native rhizobacterial isolates as biological inducers of resistance against Fusarium wilt under different organic growing media. A split-plot randomized complete block design was applied using three growing media (rice husk charcoal, manure, and their combination) and four rhizobacterial treatments (control and three local isolates: R1–R3) with three replications. Key physiological assays included the measurement of salicylic acid (SA) content and peroxidase (POX) enzyme activity as biochemical indicators of induced resistance. Results showed that the isolate from Waitii Village (R3) significantly reduced disease incidence to 52.67% compared with 86.56% in the control, while the combined organic medium (M2) further enhanced plant resistance. Increased SA (26.82 ppm) and POX activity exhibited strong negative correlations with disease incidence (R² = 0.60 and R² = 0.71, respectively), indicating their pivotal role in rhizobacteria-mediated defense activation. These findings confirm that indigenous rhizobacteria, when combined with organic amendments, effectively stimulate systemic acquired resistance and mitigate the severity of Fusarium wilt in shallots. The study highlights the potential of the R3 isolate as a sustainable bioinoculant candidate for integrated disease management. Further molecular identification, in vitro antagonism testing, and multi-location field validation are recommended to ensure its stability, efficacy, and applicability under diverse agroecological conditions.